Disparity in Orthodontic Utilization and Treatment Need Among High School Students - Suchitra Nelson, PhD; Vidya Armogan, DDS, MSD; Yumi Abei, DDS, MSD; B. Holly Broadbent, DDS, Mark Ha (Blackwell Synergy, 2004)
Theaim of this cross-sectional study was to assess the disparity in utilization of orthodontic services among high school students and to measure and characterize the extent of unmet treatment needs among untreated students at the time of examination.